A Dicationic Bismuth(III) Lewis Acid: Catalytic Hydrosilylation of Olefins. Issue 28 (12th June 2019) - Balasubramaniam, Selvakumar; Kumar, Sandeep; Andrews, Alex P.; Varghese, Babu; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract : Lewis acid promoted activation of inert chemical bonds is central to catalysis. The presence of a highly electrophilic central atom having minimum interactions with anions and solvent molecules is a requisite for a reactive Lewis acid. This requirement for a strong Lewis acid is met with by designing a reactive cation of a heavy element, bismuth, bearing the tridentate trispyrazolylborate ligand. The coordination sphere of the electrophilic bismuth dication is stabilized by very weak interactions with the halogen atoms of the weakly nucleophilic tetrakis(pentafluorophenyl)borate anion, chlorobenzene, and ortho ‐dichlorobenzene in the solid state. The high electrophilicity at bismuth is demonstrated by the ability of the dication to efficiently catalyze the addition of Si–H to olefins. Abstract : "Soft" Bismuth Working "Hard"! The first example of a highly electrophilic bismuth dication catalyzing olefin hydrosilylation under mild conditions is presented.